International Normalised Ratio Monitoring in Children: Comparing the accuracy of portable point-of-care monitors to standard of care laboratory monitoring at Red Cross War Memorial Children's Hospital - Moore, Ryan (Department of Paediatrics and Child Health, 2021)
Background. There is an increasing trend in the use of long-term oral anticoagulation therapy in children. Monitoring the international normalised ratio (INR) is an integral part in management of these patients, but standard laboratory testing of the INR presents challenges in this age group. Point-of-care INR monitors such as the Mission® PT/INR monitor provide advantages in efficiency and accessibility but have not been evaluated for accuracy in the South African paediatric setting. Objectives. This is a feasibility study with the aim to evaluate the accuracy of the Mission® PT/INR Monitor in comparison to standard laboratory INR measurement, in children presenting for INR testing. Methods. We compared the accuracy of the Mission® PT/INR monitor to the Sysmex Cs2100i laboratory analyser in 37 children aged between 1 year and 17 years, who presented for INR testing. The sample size was limited due to time constraints. 40 paired POC INR and laboratory INR values were obtained. Results. The majority of participants in the study were outpatients (62%) and required INR testing as part of screening in non-cardiac disease (81%) - the majority had chronic liver disease, and a minority were on warfarin therapy (13.5%). The mean INR value on the Mission® PT/INR was 1.49 (standard deviation (SD) 0.73) and was comparable to the Sysmex Cs-2100i (mean INR value 1.39 with SD 0.69). The Bland-Altman difference plot revealed good agreement. Bias between the two methods was 0.13 (SD 0.23). In total, 92.5% of POC INR values were within 0.5 units of laboratory INR value. Conclusion. The Mission® PT/INR point-of-care monitor has a clinically acceptable level of accuracy in children when compared with laboratory INR measurement, but larger studies are needed in the paediatric setting to evaluate patient safety and clinical outcomes. There is a need for implementing POC INR monitoring in outpatient settings but this practice will require robust assessment of infrastructure and quality control before application.